Students' Data Collection, Graph-Making, and Conclusion-Making Skills in Inquiry-based Learning Using Interactive Simulations - Pranata, Ogi Danika (META: Journal of Science and Technological Education, 2025)
This study investigates students' skills in data collection, graph-making, and conclusion-making during a basic physics course on force and motion using worksheet-integrated PhET simulations. Sixteen students at IAIN Kerinci were selected through total population sampling. Worksheets were designed to guide students through three investigative tasks: examining the effects of resultant forces, exploring the relationship between mass and acceleration under constant force, and analyzing the relationship between force and acceleration under constant mass. Quantitative descriptive and correlational methods were employed to evaluate and analyze students’ skill levels and relationships between the skills. Results indicate that students excel in data collection, achieving consistent and high scores, but face challenges in graph construction and conclusion-making, as evidenced by higher variability and errors. Significant misconceptions, such as misunderstanding the conditions of zero resultant force and acceleration, were identified. Correlational analysis revealed a strong, positive relationship between data collection and graph-making skills, but no significant correlation with conclusion-making skills. Regression analysis suggested limited predictive ability of the foundational skills for inferential reasoning. The findings underscore the need to focus on enhancing graph-making and pattern-identification processes to support conclusion-making. This research highlights critical areas for improving physics education and developing scientific reasoning skills.